Economic and legal principles of social protection of military personnel: World experience and Ukraine - Klochko, Alona; Chernadchuk, Tamara; Klietsova, Nataliia; Sherstiuk, Hanna; Bryzhan, Yurii; Kyrylenko, Volodymyr (Edelweiss Applied Science and Technology, 2024)
The article considers principles of military personnel’ social protection in Ukraine, USA, Australia, and New Zealand in a comparative perspective. The framework used for the analysis is the dilemma of two opposing concepts of countries’ development and security – ‘warfare state’ and ‘welfare state’. The detrimental effect of skewing towards warfare state, manifested in skyrocketing growth of military field expenditures, is shown, backed up with an array of statistical data, scholars’ publications and expert analytics. It is demonstrated that the arising and essence of this opposition is rooted in the growing trends of securitization throughout the world, and detrimental effects of over-securitization on the overall welfare of country are justified. It is emphasized that for Ukraine, these concerns are particularly important, especially in the current conditions of war and the need, on the one hand, to effectively protect the country from aggression and on the other hand, enable economic and social resilience.